2018
DOI: 10.1007/s11356-018-1239-4
|View full text |Cite
|
Sign up to set email alerts
|

ICT, openness and CO2 emissions in Africa

Abstract: This study investigates how information and communication technology (ICT) complements globalisation in order to influence CO emissions in 44 Sub-Saharan African countries over the period 2000-2012. ICT is measured with internet penetration and mobile phone penetration whereas globalisation is designated in terms of trade and financial openness. The empirical evidence is based on the generalised method of moments. The findings broadly show that ICT can be employed to dampen the potentially negative effect of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(100 citation statements)
references
References 73 publications
7
81
0
2
Order By: Relevance
“…The outcome variable of environmental pollution that is proxied by CO 2 emissions per capita is consistent with recent environmental pollution literature in SSA (Asongu, , ). The governance mechanisms from Kaufmann, Kraay, and Mastruzzi () are increasingly being used in the governance literature.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…The outcome variable of environmental pollution that is proxied by CO 2 emissions per capita is consistent with recent environmental pollution literature in SSA (Asongu, , ). The governance mechanisms from Kaufmann, Kraay, and Mastruzzi () are increasingly being used in the governance literature.…”
Section: Methodssupporting
confidence: 73%
“…The outcome variable of environmental pollution that is proxied by CO 2 emissions per capita is consistent with recent environmental pollution literature in SSA (Asongu, 2018a(Asongu, , 2018b. The governance mechanisms from Kaufmann, Kraay, and Mastruzzi (2010) are 1 The conception and definition of policy syndrome in the light of contemporary inclusive development literature is "inequality" or "growth that is not inclusive" (Asongu & Nwachukwu, 2017a;Tchamyou, Erreygers & Cassimon, 2018).…”
Section: Datasupporting
confidence: 60%
“…(ii) The emission of Carbon dioxide (CO 2 ) constitutes about three-quarter of emissions of green house gases globally (Akpan, 2012) and many estimates are consistent with the fact that the negative consequences of climate change will be most felt in Africa (Kifle, 2008;Asongu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Second, carbon dioxide emissions which are at an all time high (McGrath, 2018) represent a considerable challenge to environmental sustainability in the light of Sustainable Development Goals which centre on the promotion of the green economy (Asongu, le Roux & Biekpe, 2017, 2018bEfobi et al, 2019). McGrath (2018) further maintains that net outputs from green growth are not enough to dampen the growing pollution of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to African-centric literature, the studies closest to this paper are Asongu (2018b) and Asongu et al (2018a) which have respectively, established the connection between globalization and carbon dioxide emissions and the relationship between globalization and governance. In essence, Asongu (2018b) has investigated linkages between information and communication technology, globalization and carbon dioxide emissions while Asongu et al (2018a) have contributed to the empirics by establishing that various components of globalization affect governance dynamics. The current research builds on these two studies in the light of the identified shortcomings in the environmental degradation literature, to assess how globalization-moderated carbon dioxide emissions influence governance standards in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%